Interfacial energies in nanocrystalline complex oxides - Castro, Ricardo H.R. (Current opinion in solid state & materials science, 2021)
•Introduce concepts of interfacial energy modification in oxide materials.•Establishes rational behind impact of interfacial energies in nanostructural control.•Presents collections of experimental thermodynamic data on interfacial energies of oxides for benchmark. This paper presents a brief description of the role of interfacial energies in the understanding and control of nanocrystalline complex oxides in both particulate and bulk forms. Interfacial energies are fundamental parameters in microstructural evolution processes such as phase transformation, grain growth, and sintering. Although generally considered constant driving forces, experimental evidences confirm the possibility of intentional modification of both surface and grain boundary energies in oxide systems via ionic doping. This opened the perspective for a systematic understanding of their roles as refining parameters in microstructural control during processing and in operation. In this work, the theoretical framework in the context of Gibbs adsorption isotherm and the formation of dopant excess (i.e. interfacial solute segregation) is introduced in a similar manner as formalized for liquid systems. A collection of data demonstrating interfacial energy control in oxides is presented and discussed in terms of microstructural relationships with specific examples. The data advocates for a paradigm shift on nanocrystalline processing control from a traditionally kinetically oriented perspective to a more balanced viewpoint in which thermodynamics can play a governing role, especially at moderate temperatures. The work is not an extensive review, but rather has the goal of introducing the reader to this growing research topic.